2007
DOI: 10.1002/jmv.20872
|View full text |Cite
|
Sign up to set email alerts
|

Modification of rotavirus multiplex RT‐PCR for the detection of G12 strains based on characterization of emerging G12 rotavirus strains from South India

Abstract: Rotaviruses are the major etiological agents of diarrhea in children less than 5 years of age. The commonest G types in humans are G1-4 and G9. G12 is a rare human rotavirus (HRV) strain first reported in the Philippines. In this study, 13 G12 strains obtained from a community-based cohort and a hospital-based surveillance system in 2005 were characterized by phylogenetic analysis of partial nucleotide sequences of VP7, VP6, and NSP4 genes. Sequence and phylogenetic analysis of VP7 gene sequences showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
64
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 31 publications
1
64
0
Order By: Relevance
“…In a study from Kolkata (1998Kolkata ( -2000, the most predominant genotype was G1P [8], followed by G2P [4] and G4P [8]. A number of uncommon genotypes, G1P [4], G2P [8], G2P [6], G4P [4], and G4P [6] were also observed [29]. A novel rotavirus strain G4P [8] was also reported from children with acute diarrhea during that study.…”
Section: Epidemiology and Genetic Diversity Of Group A Rotavirusesmentioning
confidence: 59%
See 4 more Smart Citations
“…In a study from Kolkata (1998Kolkata ( -2000, the most predominant genotype was G1P [8], followed by G2P [4] and G4P [8]. A number of uncommon genotypes, G1P [4], G2P [8], G2P [6], G4P [4], and G4P [6] were also observed [29]. A novel rotavirus strain G4P [8] was also reported from children with acute diarrhea during that study.…”
Section: Epidemiology and Genetic Diversity Of Group A Rotavirusesmentioning
confidence: 59%
“…In a study by IturrizaGomara et al [45], a collection of over 3000 rotavirus isolates collected during 1995-1998 indicated the presence of four common types, G1P [8], G2P [4], G3P [8] and G4P [8], that constituted over 94% of typed isolates [45]. However, uncommon strains like G1P [4], G2P [8], G4P [4], G9P [6] and G9P [8] were found in smaller frequencies. In contrast, an epidemiological survey conducted in India from 1986 to 1988, showed that 70% of strains belonged to the unusual combination of G9P [11] [29,74].…”
Section: Epidemiology and Genetic Diversity Of Group A Rotavirusesmentioning
confidence: 99%
See 3 more Smart Citations